Green Antibiotic Daun Sirih (Piper betle l.) Sebagai Pengganti Antibiotik Komersial untuk Penanganan Mastitis - Gabby Lutviandhitarani; Dian Wahyu Harjanti; Fajar Wahyono (Jurnal Agripet, 2015)
(Green antibiotic betel leaf (Piper betle l.) as a substitute for commercial antibiotic in mastitis treatment)ABSTRACT. The present study was carried out to investigate the possible antibacterial activity of betel leaf on the amount and microscopic appearance of mastitis-causing bacteria. The randomized block design with 5 treatment groups were : K group (mastitis milk only as negative control), Ab group (mastitis milk + antibiotic penicillin-dihydrostreptomycin as positive control), S1 group (mastitis milk + 1,25 ml betel leaf water extract), S2 group (mastitis milk+ 2,5 ml betel leaf water extract), and S3 group (mastitis milk + 5 ml betel leaf water extract). The result showed that the amount of bacteria in the betel leaves groups (S1, S2, and S3 groups) were lower (P 0,05) than that of the control group (K group). Nonetheless the different concentration of betel leaf water extract in the S1, S2 and S3 groups did not affect to the amount of bacteria (P 0,05). Moreover, this research showed that betel leaf water extract had the same effectiveness with commercial antibiotic penicillin-dihydrostreptomycin to inhibit the growth of bacteria as indicated by the same amount of bacteria (P0,05) among the betel leaf groups (S1, S2, and S3 groups) and the Ab group. Gram-positive and negative bacteria were seen in the K group. However, only Gram-negative bacteria were visible in the betel leaf groups (S1, S2, and S3 groups) and in the Ab groups, indicating that betel leaf had the same effectiveness as penicillin-dihydrostreptomycin to inhibit the growth of Gram-positive bacteria.